2007
DOI: 10.1001/archinte.167.11.1152
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous vs Sequential Counseling for Multiple Behavior Change

Abstract: Background: Many patients in primary care settings present with multiple behavioral risk factors for cardiovascular disease. Research has provided little information on the most effective ways to approach multiple behavior change counseling in clinical settings. Methods:We implemented a randomized trial in a publicly funded primary care setting to test whether a sequential presentation of stage of change-based counseling to stop smoking, reduce dietary sodium level to less than 100 mEq/L per day, and increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 60 publications
(53 reference statements)
7
122
2
1
Order By: Relevance
“…However, other recent interventions in primary care or general medicine settings have been effective [7,[80][81][82][83], though challenging to implement [84], so this area may also be worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, other recent interventions in primary care or general medicine settings have been effective [7,[80][81][82][83], though challenging to implement [84], so this area may also be worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, targeting exercise, dietary sodium intake, and tobacco use using a stage-based approach concluded that sequential was not superior to, and may be inferior to, a simultaneous approach (Hyman, et al, 2007). The theoretical model employed and the types of behaviors targeted certainly may influence the efficacy of a simultaneous versus a sequential approach.…”
Section: Or Diabetes (Diabetes Prevention Programmentioning
confidence: 99%
“…The final sample consisted of 14 articles (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) , in compliance with literature, which recommends that at least 30% of articles attending to the established inclusion criteria be included (5) .…”
Section: Identification Of Review Problemmentioning
confidence: 99%
“…Instruments were frequently used to quantify the duration, intensity and frequency of PA. Most studies (64.3%) used biological markers, such as maximum oxygen consumption, serum cholesterol levels and body mass index (BMI) (7,11,(14)(15)(16)(17)(18)(19)20) and half of them applied physical tests, such as load and walking tests (8,11,(14)(15)(17)(18)20) (Table 1). …”
Section: Study Categorization Analysis and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation